Elections to the Yekaterinodar gorsky verbal court: strengthening the russian influence on cherkess aul societies (beginning of the 1870s) - Ruslan Sultanovich Kandor (Вестник Майкопского государственного технологического университета, 2023)
The article considers the historical experience of the formation of the first mountain verbal court in the Yekaterinodar uyezd of the Kuban region. In 1864 there was a need to strengthen the Russian influence on aul administrations due to the implementation of the judicial reform in the North Caucasus. Formation of the regional judicial system and the legal foundations of legal proceedings in the post-reform period is always of great interest to researchers. Knowing positive and negative examples in the historical experience of implementing reforms in various ethnic and religious communities is always relevant and is of particular importance for educating generations of young reformist administrators. In the article the author followed the principle of science and the principle of objectivity in conducting research, he used a corresponding wide range of sources on the history of the Adyghs (Circassians), which included a large amount of archival material, assuming a comprehensive coverage of historical facts on the problem. The principle of historicism also plays an important role in the study of the problem, which allowed us to consider the activities of the civil authorities of the Kuban region in the process of reforming the mountain judicial system in dynamics from actual events in specific historical conditions in close connection with the administrative policy of the state to theoretical considerations about their causes and consequences. The article reveals the activities of the civil authorities of the Kuban region to maintain a peaceful situation in the Circassian villages of the Yekaterinodar Uyezd and to prevent disturbances, provoked during the formation of the first composition of the Yekaterinodar Mountain Verbal Court. Disturbances in the Circassian villages were stopped and control over the village administrations was restored due to the efforts of Lieutenant General Karmalin. The author concludes that a certain periodicity of the outbursts of provocations that aroused the minds of residents of the Circassian villages were of foreign origin, generating more and more demands on the Russian authorities.